The role of social workers in the prevention of adolescent pregnancy in Oyo east local government area, Oyo State (2019)
The study investigated the role of Social Workers in the prevention of adolescent pregnancy in Oyo East Local Government Area of Oyo State, Nigeria. It has been observed that unwanted pregnancy is popular among adolescents resulting in most of them dropping out of school. Specifically, the objectives of the study are to ascertain the factors associated with adolescent pregnancy and to establish social work intervention strategies for adolescent pregnancy. The population for the study consisted of 27 social workers in social work department of state hospitals, health centers, primary and secondary schools as well as social welfare organizations spread across 16 different locations in Oyo East Local Government Area of Oyo state. Total enumeration sampling technique was used to sample the 27 social workers. Questionnaire was used to gather relevant data. The findings revealed that poverty (100%), child abuse (100%), child abandonment 100%, and lack of sex education (92.6%) predisposed adolescents to early or unwanted pregnancy. However, Social Workers adopted improving communication between parents and their children (85.2%), community-based prevention (85.2) and encouraging adolescents to attain higher education (100%) as major intervention strategies to prevent adolescent pregnancy among teenagers. The study therefore recommends that Local Government Authority in collaboration with the state government should employ the Services Social Workers who have the competence and skills to address the root causes of adolescent pregnancy in order to prevent adolescent pregnancy. Also parents should instill sound moral teachings in their children and collaborate with social workers to provide effective sex education for teenagers